2005
DOI: 10.1259/dmfr/24863557
|View full text |Cite
|
Sign up to set email alerts
|

The utility of panoramic radiography in temporomandibular joint assessment

Abstract: Morphological condylar abnormalities are present on panoramic images in all adult age ranges, regardless of status of the dentition or presence of TMD. Condylar shape alone is not an indicator of TMD, and minor condylar discrepancies may have no significance in TMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 18 publications
4
48
0
3
Order By: Relevance
“…Crow et al documented osteophytic changes in 42% of their subjects without TMJD, and evident osteophytes in 7%. The same authors observed mild condyle flattening in 74% of the subjects without TMJD, and severe flattening in 15% (20). Adaptive bone remodeling can induce changes similar to those of osteoarthrosis, and this could explain the high prevalence of radiological alterations in healthy individuals.…”
Section: Discussionmentioning
confidence: 89%
“…Crow et al documented osteophytic changes in 42% of their subjects without TMJD, and evident osteophytes in 7%. The same authors observed mild condyle flattening in 74% of the subjects without TMJD, and severe flattening in 15% (20). Adaptive bone remodeling can induce changes similar to those of osteoarthrosis, and this could explain the high prevalence of radiological alterations in healthy individuals.…”
Section: Discussionmentioning
confidence: 89%
“…Crow et al (13) found that in panoramic radiography, there are no differences in condylar morphology between patients with and without TMJ disorders. The prevalence of condylar bone changes in orthognathic surgery patients has been reported to be 55% by transpharyngeal radiographs (14) and 35.7% by CT (15).…”
Section: Discussionmentioning
confidence: 99%
“…8 Previous studies attempting to correlate pain intensity levels with the quality of bony changes in TMJ OA using different imaging modalities were equivocal. [9][10][11] The aim of this study is to determine whether condylar changes in TMJ OA (based on CBCT images) is correlated with pain and other clinical signs and symptoms.…”
Section: Introductionmentioning
confidence: 99%